Village voices, forest choices pioneering India's forest management - Poffenberger, Mark 1950-.; McGean, Betsy (Delhi Oxford University Press, 1994)
Contributed articles concerning grassroots forest movements in India.
October 1994
Keywords: Community forests -- Management. -- India; Forest management -- Citizen participation. -- India